1994
DOI: 10.1002/crq.3900110306
|View full text |Cite
|
Sign up to set email alerts
|

Mediator issue intervention strategies: A replication and some conclusions

Abstract: The goal of the study reported here was to compare two samples of mediator intervention strategies to learn about sources of dissatisfaction among clients. The results indicate that the more mediators ignore disputants' relational concerns, the more difficulty they will experience in reaching agreement. In both samples, couples who came to mediation with significant relational baggage quickly moved the discussion toward these concerns and away from substantive issues. Mediators who had trouble reaching agreeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 7 publications
2
19
0
Order By: Relevance
“…In a recent replication study, Donohue, Drake, and Roberto (1994) confirmed these earlier findings, adding that the court-based mediators whom they studied failed to help clients with their deeper relational problems, which were especially evident in couples that failed to reach agreement. Donohue, Drake, and Roberto suggested that this disinclination to deal with relational issues may reflect state law that constrains what court-based mediators can discuss (see .…”
Section: Research In Family Mediation: a Review In Three Partssupporting
confidence: 52%
See 1 more Smart Citation
“…In a recent replication study, Donohue, Drake, and Roberto (1994) confirmed these earlier findings, adding that the court-based mediators whom they studied failed to help clients with their deeper relational problems, which were especially evident in couples that failed to reach agreement. Donohue, Drake, and Roberto suggested that this disinclination to deal with relational issues may reflect state law that constrains what court-based mediators can discuss (see .…”
Section: Research In Family Mediation: a Review In Three Partssupporting
confidence: 52%
“…Only services that employ a therapeutic model of service, and thus are designed to effect such changes and allot adequate time to do so, are likely to report change in coparental relations. Support for this therapeutic argument comes from Donohue and his colleagues (Donohue, Lyles, and Rogan, 1989;Donohue, Drake, and Roberto, 1994;Burrell, Donohue, and Allen, 1988;Donohue, 1989,199 1;Donohue and Weider-Hatfield, 1988;Donohue, Diez, and Weider-Hatfield, 1984;Donohue, Allen, and Burrell, 1985, 19881, who have documented that court-based services typically offer less than four hours of service, and that the tendency of mediators in that setting is to focus on facts and issues and avoid relational processes. Conversely, Kressel and others (19941, Johnston, Campbell, and Tall (1985), and Matheson and Gentleman (1986) have documented the great extent to which mediators operating in private settings concentrate as much or more on relationship processes as on facts.…”
Section: Research In Family Mediation: a Review In Three Partsmentioning
confidence: 99%
“…Couples with serious relationship problems were less likely to reach agreements, particularly when there was no opportunity in mediation to deal with the problems or when the style of the mediator was to deal only with facts. Agreement rates in custody disputes were affected by the number of issues in dispute (Donahue et al, 1994). However, mediation involving an ongoing relationship between disputants and involving multiple issues to resolve was more predictive of resolution than mediation involving single issue, nonrelated disputants (Whiting, 1994).…”
Section: Implications For Couples and Family Counselorsmentioning
confidence: 95%
“…Most of these studies have been in family mediation rather than small claims settings. Donahue, Drake, and Roberto (1994) found parties less likely to reach agreement if when mediators ignore relational concerns. In the long term (6 months later), reflecting strategies were associated positively with an increase in parties' willingness to consider the other parent's perspective, prioritization of their children's needs, and desire to have a positive relationship with the other parent (Charkoudian et al, 2018).…”
Section: Relational Strategiesmentioning
confidence: 99%